OTULIN deficiency in ORAS causes cell type‐specific LUBAC degradation, dysregulated TNF signalling and cell death - Rune Busk Damgaard; Paul R Elliott; Kirby N Swatek; Eamonn R Maher; Polina Stepensky; Orly Elpeleg; David Komander; Yackov Berkun (EMBO Molecular Medicine)
Abstract The deubiquitinase OTULIN removes methionine‐1 (M1)‐linked polyubiquitin signals conjugated by the linear ubiquitin chain assembly complex (LUBAC) and is critical for preventing TNF‐driven inflammation in OTULIN‐related autoinflammatory syndrome (ORAS). Five ORAS patients have been reported, but how dysregulated M1‐linked polyubiquitin signalling causes their symptoms is unclear. Here, we report a new case of ORAS in which an OTULIN‐Gly281Arg mutation leads to reduced activity and stability in vitro and in cells. In contrast to OTULIN‐deficient monocytes, in which TNF signalling and NF‐κB activation are increased, loss of OTULIN in patient‐derived fibroblasts leads to a reduction in LUBAC levels and an impaired response to TNF. Interestingly, both patient‐derived fibroblasts and OTULIN‐deficient monocytes are sensitised to certain types of TNF‐induced death, and apoptotic cells are evident in ORAS patient skin lesions. Remarkably, haematopoietic stem cell transplantation leads to complete resolution of inflammatory symptoms, including fevers, panniculitis and diarrhoea. Therefore, haematopoietic cells are necessary for clinical manifestation of ORAS. Together, our data suggest that ORAS pathogenesis involves hyper‐inflammatory immune cells and TNF‐induced death of both leukocytes and non‐haematopoietic cells.